2018
DOI: 10.1016/j.biomaterials.2018.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Rapid 3D bioprinting of decellularized extracellular matrix with regionally varied mechanical properties and biomimetic microarchitecture

Abstract: Hepatocellular carcinoma (HCC), as the fifth most common malignant cancer, develops and progresses mostly in a cirrhotic liver where stiff nodules are separated by fibrous bands. Scaffolds that can provide a 3D cirrhotic mechanical environment with complex native composition and biomimetic architecture are necessary for the development of better predictive tissue models. Here, we developed photocrosslinkable liver decellularized extracellular matrix (dECM) and a rapid light-based 3D bioprinting process to patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
208
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 231 publications
(209 citation statements)
references
References 41 publications
(60 reference statements)
1
208
0
Order By: Relevance
“…While the physical properties of synthetic polymers are easily controllable, they generally exhibit poor biocompatibility, toxic degradation products, and lack of bioactivity . The utilization of dECM as a bioink for 3D printing of tissue engineered constructs is, therefore, increasingly being employed by numerous research groups . For its printing, the dECM must first be solubilized or “fluidized” to enable its extrusion through the printing apparatus.…”
Section: Decm Processing Approachesmentioning
confidence: 99%
See 3 more Smart Citations
“…While the physical properties of synthetic polymers are easily controllable, they generally exhibit poor biocompatibility, toxic degradation products, and lack of bioactivity . The utilization of dECM as a bioink for 3D printing of tissue engineered constructs is, therefore, increasingly being employed by numerous research groups . For its printing, the dECM must first be solubilized or “fluidized” to enable its extrusion through the printing apparatus.…”
Section: Decm Processing Approachesmentioning
confidence: 99%
“…Processed dECM‐based models are extensively being developed for the investigation of tumor biology . A glioblastoma multiforme (GBM) brain tumor model was developed combining decellularized patient‐specific GBM‐derived hydrogel and patient‐derived GBM cells ( Figure a) .…”
Section: Applications Of Processed Decm‐based Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 7 details the 3D bioprinting scheme for this tri-culture liver model, which has significant potential for pathophysiological studies with a patient-specific platform and early drug screening. In a different report, 3D bioprinted liver decellularized ECM scaffolds were created with tailorable mechanical properties to mimic regional stiffness in the cirrhotic liver [142]. Using this model, the authors showed that HepG2, a human liver cancer cell line, displayed stromal invasion from the nodule with cirrhotic stiffness.…”
Section: Of 40mentioning
confidence: 99%